COVID-19 pandemic and its influence: Case study in North Bengal Medical College, Darjeeling district, West Bengal, India - Nilanjana Ghosh (Wolters Kluwer Medknow Publications, 2022)
COVID-19 pandemic will be the most dreaded public health challenge world has ever faced and health-care workers play a crucial role in combating it, risking their own lives. Health workers serving COVID faced discrimination. Many new set up like COVID-19 screening clinics with complete new set of rules and logistics were set up. In North Bengal Medical College (NBMCH), it was functional round the clock since its inception. Our case that was a chronic smoker, alcoholic, and had records of defiant behavior was posted as a guard here. The anguish and pan of the patients attending, an increased job responsibility thrust on him along with the dependence of patients on his behavior brought about a change. Witnessing able tireless fearless leaderships from major wards, supportive supervision, empathy, and regular counseling sessions are thought to herald the positive behavioral change in him. The role of self-actualization theories and adoption of behaviors with effective health communications and theories of ergonomics were reinstated. Using health belief models, a deep understanding of the preventive behaviors was tried.